POLA KOMUNIKASI POLITIK ANIES BASWEDAN DALAM PERSPEKTIF SOSIOLINGUISTIK DI MEDIA SOSIAL INSTAGRAM - Nurul Hidayah; Ratna Dewi Kartikasari (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2021)
Political communication is a form of the process of delivering a message from a regional head to the community. By using the choice of speech code according to its purpose and function, political communication can certainly work. The purpose of this research is to analyze a speech pattern of Anies Baswedan in political communication on Instagram social media. The data was collected using the observation method. In carrying out this observation method, basic techniques are applied, namely tapping techniques which are then continued with advanced techniques in the form of competent free listening techniques, recording techniques and note-taking techniques. Data analysis was performed using the equivalent method, contextual method, and was carried out using the markup reading technique. Based on the results of data analysis, Anies Baswedan used the choice of speech code as a communication need in accordance with his speech function. The form of speech code choices used varies. The pattern of choice of speech code for Anies Baswedan as regional head in political communication on Instagram social media is classified into two parts, namely based on the relationship between participants and the surrounding situation. Anies Baswedan in making speech code choices has a variety of patterns with the dominant patterns that emerge based on participant relationships, namely vertical patterns and informal patterns. Keywords: Anies Baswedan, Sociolinguistics, Patterns of Political Communication